GENERATION MEAN ANALYSIS USING GENERATION VARIANCE IN MAIZE TRAITS - & et.al, Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to evaluate the effect of gene action on grain yield and yield components of maize(Zea mays L.) using generation mean analysis method for six generations (P₁, P₂, F₁,F₂, Bc₁ and Bc₂ )of two crosses of maize (H40×un44052)and (Ik8×Hs). The analysis of variance shows significant differences between generation means. Generation mean analysis revealed that the non-additive effect for plant height, No.of kernels row-1, 300- kernel weight and grain yield plant-1. In addition the result showed that complete and additive × additive variance were positive values for all traits, This is an indicator of the presence of complete dominance for those characteristics. The results indicated that the broad sense heritability values were more than the narrow sense heritability values. Positive heterosis was revealed for plant height and kernel yield plant-1 in both crosses.